LINGUISTIC THEORY AND MARKETING TOURISM - Dias, Naveen A. H (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Linguistic theories have a long history. A speaker’s linguistic competence is extraordinary. He or she has the capacity to generate infinite number of sentences, using the basic rules of grammar. Meaning is also equally important in linguistics. British applied linguists like D.A.Walkins, Christopher Candlin, Henry Widdowson, Christopher Brumfit, Keith Johnson, and functional linguists like J.R. Firth and M.A.K. Halliday brought about significant shifts to approach, methods and techniques in language pedagogy. Importance was given to the social situations in which the language is used and the social roles of the learners and users of the language. This led to the sociolinguistic views and brought changes in the syllabi, where situation, roles, topics, settings and activities and tasks played dynamic roles.